Workplace morality : behavioral ethics in organizations - Kaptein, Muel, 1969- (Bingley : Emerald Group Pub. Ltd., 2013)
Why do honest and decent employees sometimes overstep the mark? What makes managers with integrity go off the rails? What causes well-meaning organizations to deceive their clients, employees and shareholders? Social psychology offers surprising answers to these intriguing and timely questions. Drawing on scientific experiments and examples from business practice, Muel Kaptein discusses why good people sometimes do bad things and how they rise above this behavior. He explains why cheats wear sunglasses, why overstepping the mark could be a good thing, how a surplus of rules creates offenders and why we should be suspicious of colleagues who wash their hands after meetings.
Contents note continued: 43.A Problem Shared is a Problem Halved: Communication Theory -- 44. What You See Is not What You Say: Group Pressure and Conformity -- 45. Explaining, Speaking Out, and Letting off Steam: Pressure Build-Up Under Thought Suppression -- 46. Blow the Whistle and Sound the Alarm: The Bystander Effect and Pluralistic Ignorance -- Factor 7 Enforcement -- 47. The Value of Appreciation: Compliments and the Midas Effect -- 48. Washing Dirty Hands: Self-Absolution and the Macbeth Effect -- 49. Punishment Pitfalls: Deterrence Theory -- 50. The Price of a Penalty: The Crowding-Out Effect -- 51. The Corrupting Influence of Rewards and Bonuses: The Overjustification Effect -- 52. The Heinz Dilemma: Levels of Moral Development.
Includes bibliographical references (p. [131]-161).
Keywords: Business ethics; Employee morale; Organizational behavior -- Moral and ethical aspects